Nursing Care for the Elderly with Dementia: A Case Study of Application in the Working Area of Tanjung Paku Health Center, Solok City - Aini Yusra; Syahrum; Azizah Gusril; Abdul Gafar (Journal of Applied Holistic Nursing Science, 2025)
Background: Dementia, a progressive cognitive decline syndrome affecting memory, orientation, and daily activities, is a global health concern. At Tanjung Paku Health Center, Solok City, five cases of dementia in the elderly were recorded from January to December 2024 out of 315 total elderly individuals, highlighting the urgency of comprehensive nursing care. Objective: This study aims to describe nursing care for the elderly with dementia, from assessment to evaluation. Method: Using a descriptive design with a single case study approach, the research was conducted from March 24-29, 2025, in RT 001/RW 006, Tanjung Paku Village, Solok City. The subject was one elderly person (Medical Record No. 003574) selected by purposive sampling based on inclusion criteria. Nursing care involved data collection and analysis, diagnosis formulation, intervention planning, action implementation, and evaluation of changes in the patient's condition. Results: The patient exhibited primary symptoms of dementia such as frequent forgetfulness, difficulty recalling past events, verbal communication and comprehension difficulties, and blurred vision. Environmental observation revealed a high fall risk due to the absence of handrails in the bathroom. Nursing diagnoses established were impaired memory, impaired verbal communication, and risk for falls. Implemented interventions included memory exercises (puzzle play therapy), communication strategies for hearing deficits, and fall prevention. Conclusion: Comprehensive nursing care is crucial in addressing cognitive impairment, communication issues, and physical safety problems in elderly individuals with dementia. Specific interventions like puzzle therapy and family education show positive potential in symptom management and improving patient quality of life.